2011
DOI: 10.1007/s00392-011-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Septic cardiomyopathy: hemodynamic quantification, occurrence, and prognostic implications

Abstract: By using the parameter "afterload-related cardiac performance, ACP", the impairment of cardiac function can be reliably quantified showing that septic cardiomyopathy occurs frequently and is of prognostic relevance in patients with septic MODS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 19 publications
3
47
0
6
Order By: Relevance
“…These results are consistent with those obtained in other conditions not associated with coronary artery disease, such as supraventricular tachyarrhythmias, acute pulmonary embolism, sepsis, stroke, and strenuous exercise [30][31][32][33]. The magnitude of the increase in troponin levels is generally less and persists for a shorter period of time compared with the troponin increases associated with acute myocardial infarction.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those obtained in other conditions not associated with coronary artery disease, such as supraventricular tachyarrhythmias, acute pulmonary embolism, sepsis, stroke, and strenuous exercise [30][31][32][33]. The magnitude of the increase in troponin levels is generally less and persists for a shorter period of time compared with the troponin increases associated with acute myocardial infarction.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies revealed that the pharmacokinetics of echinocandins in special patient populations might impact clinical efficacy and safety (6). Septic cardiomyopathy is a wellknown organ dysfunction in sepsis, which is associated with reduced left ventricular contractility (19). Our study demonstrates cardiac depression and a reduced time to hemodynamic failure after administration of clinically used doses of anidulafungin (2.5 mg/kg BW) and caspofungin (0.875 mg/kg BW) in endotoxemic rats.…”
Section: Discussionmentioning
confidence: 57%
“…Most clinical and experimental studies of cardiac function in sepsis have focused on evaluation of inotropic properties (2, 6-8). The presence of myocardial depression after adequate fluid resuscitation is characteristic of severe sepsis and indicative of intrinsic cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%